The Geopolitical Problems of Eritrea - عطا الله سليمان هناء عبد الحر يوسف (College of Education for Women, 2019)
The subject of multi- ethnics is one of the most important subjects in the study of political geography, as multi- ethnics and its consequent problems are global geopolitical phenomena that started early and reached its peak with the beginning of the twentieth century, because of major changes in the political landscape that resulted by wars and led to the collapse of many empires and major powers, a matter which led to put new political maps according to certain considerations of the colonial powers, especially in Africa and Asia. All these things led to the most serious challenges based on ethnic and sectarian conflict and led to the development of geopolitical problems. Among the examples what most countries in the Horn of Africa have suffered from, especially Eritrea, which is considered as a good example for countries that suffers from multi-ethnic problems. Among the most important ethnic groups that are related to the problems of Eritrea are the Afar, Beja, and Altgerin. These three geopolitical ethnics make many problems to Eritrea and neighboring countries. What increases the seriousness of this situation is the geographical distribution of these ethnic groups in Eritrea and neighboring countries as shown in map 1.The presence of Afar, Beja and Altgerin in neighboring countries is a problem that has geopolitical dimensions that affects in the national security of Eritrea as Al- Afar occupies about 9.5% of the area of the neighboring country of Ethiopia, as well as most land in Djibouti is inhabited by Alafrien. Such situation increases the danger on security of Eritrea especially the existence of these ethnics lies in the most important geo-strategic dimension, as they live in Massawa that lies on The Red Sea and along the coast till the Dahlak Islands, which makes it among the most important geopolitical challenges to Eritrea. This danger is not related only to the Afar, but it includes other ethnicities such as the Beja and Altgerin which extend on the borders of Eritrea and the neighboring countries, and threaten the security of Eritrea, especially from its neighbor Ethiopia.